2023
DOI: 10.3390/d15121214
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Composition and Environmental Relations of Periphytic Rotifer Assemblages in Lentic Freshwater Bodies (Flanders, Lower Belgium)

Luc Denys,
Willem H. De Smet

Abstract: Periphytic rotifer assemblages from lentic habitats are understudied. To improve knowledge on the principal environmental determinants of their structure and composition, we examined summer periphyton from 184 freshwater bodies from a taxonomic and multi-trait-based perspective. Only the latter allowed consideration of all bdelloids. Alpha diversity decreased with electrolyte and aluminium concentration but increased with macrophyte richness, pointing at salinization, metal toxicity and loss of structural nich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 212 publications
0
2
0
Order By: Relevance
“…Filinia terminalis, B. calyciflorus, T. porcellus, and two species of the genus Polyarthra do not react or react positively to temperature rise. Denys and De Smet [134] identified 22% of the observed taxa as useful pH indicators, most of them in non-alkaline waters. For instance, Denys and De Smet [134] reported that pH/alkalinity and trophic conditions explained most of the variation in rotifer assemblage composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filinia terminalis, B. calyciflorus, T. porcellus, and two species of the genus Polyarthra do not react or react positively to temperature rise. Denys and De Smet [134] identified 22% of the observed taxa as useful pH indicators, most of them in non-alkaline waters. For instance, Denys and De Smet [134] reported that pH/alkalinity and trophic conditions explained most of the variation in rotifer assemblage composition.…”
Section: Discussionmentioning
confidence: 99%
“…Denys and De Smet [134] identified 22% of the observed taxa as useful pH indicators, most of them in non-alkaline waters. For instance, Denys and De Smet [134] reported that pH/alkalinity and trophic conditions explained most of the variation in rotifer assemblage composition. Although less important morpho-structural features of water bodies, their general setting and spatial context do not appear to be insignificant.…”
Section: Discussionmentioning
confidence: 99%